EFEKTIFITAS INSENTIF PAJAK UNTUK PERCEPATAN PEMULIHAN PEREKONOMIAN - Rizky Bintang Setiawan; Eka Sri Hartati (Ikatan Dosen Menulis, 2024)
The COVID-19 pandemic that occurred in mid-March 2020 in Indonesia caused economic conditions to decline drastically. The state budget deficit rose 1.7 percent from the percentage GDP. Economic growth in the first quarter of 2020 only reached 2.97 percent and fell to negative 5.32 percent in the second quarter. If there is another decline in the third quarter, it will be in a recession. However, this has not happened yet because tax revenues began to improve in June 2020. Thus, the study aims to explain the effectiveness of tax incentives that accelerating the recovery of the national economy after COVID-19. Using qualitative methods with textual data to analyze phenomena. State revenues and tax revenues have increased from the first semester to the end of July 2020 amounting to Rp. 111 trillion and Rp. 86.1 trillion. Tax incentive income of Rp. 16.6 trillion. The more tax incentives used by taxpayers have an effect on tax revenue and state revenue so as to accelerate the recovery of the national economy. The government will implement a tax incentive policy until 2021 and allow a GDP budget deficit limit of more than 3 percent by the end of the 2022 fiscal year.